A FULL DELIBERATION OF THE BRAZILIAN SUPREME COURT FOR THE EFFECTIVE CREATION OF BINDING PRECEDENTS: A VIEW OF THE DELIBERATIVE PROCEDURE OF THE US SUPREME COURT - Panutto, Peter (Revista da Faculdade de Direito do Sul de Minas, 2021)
The paper concerns the implementation – by the Brazilian Civil Procedure Code of 2015 – of a binding judicial precedent system and the consequent need to adjust the collegiate voting procedures of the Brazilian Supreme Court and other counties’ courts, so that precedent-generating decisions are the result of full collegial deliberation, with institutional recognition of precedents. The models of collegiate decision analyzed are seriatim, per curiam and majoritarian practice, concluding that the latter, which is adopted by the US Supreme Court, is more appropriate for the Brazilian Supreme Court. The purpose of this paper is to demonstrate that the inadequacy of the deliberative procedure will result in the ineffectiveness of this precedents system. The method adopted is hypothetical-deductive, through a critical analysis of the need for improvement in the process of creation and respect of precedents.